Sick leave before, during and after pregnancy - Karsten Marshall Elseth Rieck; Kjetil Telle (Statistics Norway, Research Department, 2012)
Using registry data on every employed Norwegian woman giving birth to her first child during the period 1995-2008, we describe patterns of certified and paid sick leave before, during and after pregnancy. By following the same women over time, we can explore how observed sick leave patterns are - or are not - related to the women's exiting (or reentering) employment. The results show that sick leave increases abruptly in the month of conception, and continues to grow throughout the term of pregnancy. Sick leave during pregnancy has been rising substantially compared with pre-pregnancy levels over the period 1995-2008, but this increase seems unrelated to women's growing age at first birth. In line with hypotheses of women's "double burden", observed sick leave rates increase in the years after birth. However, when we handle some obvious selection issues - like sick leave during a succeeding pregnancy - the increase in women's sick leave in the years after birth dissolves. Overall, we find little, if any, sign of the relevance of "double burden" hypotheses in explaining the excessive sick leave of women compared with men.
Keywords: C23; H55; I18; J13; J22; 330; sick leave; pregnancy; female employment; double burden.